Predicting whistleblowing intention using the whistleblowing triangle - Putu Wenny Saitri; I Wayan Suartana; Eka Ardhani Sisdyani; I Ketut Sujana (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: The increasing number of fraud cases has significantly raised the whistleblower mechanism's role. Therefore, this study investigates the impact of the whistleblowing triangle on whistleblowing intention. The whistleblowing triangle combines the theory of fraud triangle and the theory of planned behavior to predict whistleblowing intention. The reporting system is required in an organization expected to strengthen the fraud prevention system related to increasing fraud cases.Design/Methodology/Approach: This research was conducted in the village credit institution listed in Denpasar. This selection was due to Denpasar having become Bali's second-highest number of fraud cases. Thus, it is necessary to understand whether the whistleblowing triangle can deter fraud. The research sample was selected among Village Credit Institution (VCI) employees in Denpasar using accidental sampling and generating 80 employees as respondents. This study used multiple regression analysis to test the hypotheses.Research findings: The results revealed that the whistleblowing triangle's components impacted whistleblowing intention. The intention to report fraudulent behavior was negatively impacted by pressure, while it was positively affected by opportunity and rationalization.Theoretical contribution/Originality: Most previous studies have investigated whistleblowing intention using the fraud triangle and theory of planned behavior separately. Meanwhile, this study used the whistleblowing triangle, combining fraud and planned behavior theory to predict whistleblowing intention.Research limitation: This study omitted financial incentives included in the previous research.